Pengaruh Kepemimpinan Transformasional, Motivasi dan Kepuasan Kerja terhadap Kinerja PNS di BKPSDM Kabupaten Blitar - Ida Afianti (REVITALISASI : Jurnal Ilmu Manajemen, 2020)
The Purpose of this study is to determine impact of transformasitional leadership, motivation and job satisfaction both simultaneously and partially to the performance of Civil Service Personnel Agency and Human Resource Development Blitar Regency. Research type is explanatory research with multiple linear regression analysis. The result of this study, there is significant and positive impact of transformational leadership to the performance of Civil servant of Personnel Agency and Human Resource Development of Blitar Regency. There is significant and positive impact of motivation to the performance of Civil Service Personnel Agency and Human Resource Development Blitar Regency. There is significant and positive impact of job satisfaction on the performance of Civil service Personnel Agency and Human Resource Development Blitar Regency. There is significant and positive impact of transformational leadership, motivation and job satisfaction simultaneously and partially to the performance of Civil Service Personnel Agency and Human Resource Development Blitar Regency.